The Make a match learning model on critical thingking ability in PKn Learning in class IV SD Muhammadiyah 32 Medan - Yasa, Ima (Berpusi Publishing, 2023)
The background of this research is students whose critical thinking skills are still lacking and are still limited so that students have not been able to understand the concept of critical thinking and have not mastered critical thinking in Civics learning. The purpose of this study was to determine the effect of the make a match learning model on the critical thinking skills of fourth grade students at SD Muhammadiyah 32 Medan. The population in this study were all 20 students in grade IV. The sampling technique in this study used a total sampling technique. The sample in this study amounted to 20 students with 1 class. This research instrument uses a test sheet. Data analysis techniques in this study used validity tests, reliability tests and hypothesis testing. The results of this study show that the make a match learning model has an effect on students' critical thinking skills, because in the t-test analysis (independent t-test) the results of a significance value (sig. 2-tailed) are 0.000 <0.05, then Ha is accepted and Ho rejected. This means that there is an influence of the make a match learning model on students' critical thinking skills in Pkn learning in class IV SD Muhammadiyah 32 Medan. The results of data analysis obtained the average (mean) after being given treatment using the make a match learning model in the pretest class, namely 75.25. While students in the posttest class average (mean) without being given treatment with the make a match learning model is 90.55